(untitled) (Erudita: Journal of English Language Teaching, 2025)
In the implementation of language teaching curriculum, textbooks serve an indispensable purpose. The realization of the embedded potential in textbooks or any curriculum material, however, depends on how they are used in the delivered instruction. As there are few studies in the English Language Teaching context that studied combining textbook use or adaptation with the learning opportunities it results, this study investigates the way teachers adapt textbooks and how it influences the learning experiences provided in the curriculum. A qualitative case study design was adopted based on data from larger research that investigates curriculum materials use in the middle school context. The findings revealed that the two prominent adaptation techniques the teachers used, ’addition’ and ’omission’, determine the potential learning opportunities. ‘Addition’ was employed to enhance ‘form-focused learning’ and to address exam-related needs and this purpose was achieved. Resulted from ‘omission, however, the appropriate balance of language skill development could not be realized, and also opportunities for higher-order thinking skills development were denied. These findings suggest that adaptation practices need to be informed by principles that steams from pedagogical theory rather than on immediate and contextual determinants for integrating the affordances within the textbook.